Ground Demonstration of the Use of Limnospira indica for Air Revitalization in a Bioregenerative Life-Support System Setup: Effect of Non-Nitrified Urine–Derived Nitrogen Sources - Sachdeva, Neha; Poughon, Laurent; Gerbi, Olivier; Dussap, Claude-Gilles; Lasseur, Christophe; Leroy, Baptiste; Wattiez, Ruddy (Frontiers in Astronomy and Space Sciences, 2021)
Long-duration human space missions require considerable amounts of water, oxygen, and nutritious biomass. Additionally, the space vehicles must be well equipped to deal with metabolic human waste. It is therefore important to develop life-support systems which make these missions self-sufficient in terms of water, food, and oxygen production as well as waste management. One such solution is the employment of regenerative life-support systems that use biological and chemical/physical processes to recycle crew waste, revitalize air, and produce water and food. Photosynthetic cyanobacteria Limnospira could play a significant role in meeting these objectives. Limnospira can metabolize CO2 and nitrogen-rich human waste to produce oxygen and edible biomass. So far, life-support system studies have mainly focused on using chemical/physical methods to recycle water, degrade human waste, and recycle CO2 into oxygen. Nowadays, additional microbial processes are considered, such as nitrification of urea–ammonium–rich human waste and then using the nitrate for cyanobacterial cultivation and air vitalization. This cascade of multiple processes tends to increase the complexity of the life-support systems. The possibility of using non-nitrified urine for Limnospira cultivation can partially solve these issues. Our previous studies have shown that it is possible to cultivate Limnospira with urea and ammonium, the prominent nitrogen forms present in non-nitrified urine. In this study, we investigated the possibility of cultivating Limnospira with the different nitrogen forms present in non-nitrified urine and also evaluated their effect on the oxygen production capacity of Limnospira. For this 35-day-long study, we worked on a simplified version of the European Space Agency’s MELiSSA. During this ground demonstration study, we monitored the effect of urea and ammonium (vs. nitrate) on the oxygen production capacity of Limnospira. A deterministic control law, developed and validated on the basis of a stochastic light-transfer model, modulated (increase/decrease) the incident light on the photobioreactor (with Limnospira) to control oxygen levels in the closed loop. The CO2 from the mouse compartment was recycled as a carbon source for Limnospira. We observed that while the system could meet the desired oxygen levels of 20.3% under the nitrate and urea regime, it could only reach a maximum O2 level of 19.5% under the ammonium regime.